LEGAL PROTECTION OF PORNOGRAPHIC BEHAVIOR THROUGH SOCIAL MEDIA IN INDONESIA - Titus Adhi Sanjaya; Ramlani Lina Sinaulan; Mohamad Ismed (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2022)
This study aims to analyze and find legal protection against pornographic behavior in the context of divergent legal perspectives and the right to work, particularly via social media, as well as legal certainty and protection regarding the application and behavior of action porn and pornographic activities in Indonesia. This study is a descriptive analytic study. This study takes a normative legal approach through the use of the statutory approach and the conceptual approach. Researchers collect legal materials using the following strategies: Literature Studies, that is data collection techniques including the collection of reading materials, such as laws and regulations, as well as documents pertaining to the aforementioned issues. This technique is used to look for concepts, hypotheses, or viewpoints on a subject. The finding reveals that Criminal acts or pornographic crimes committed via mass/social media are prohibited under several laws, including the Criminal Code, Law No. 8 of 1992 concerning film, Law No. 36 of 1999 concerning telecommunications, Law No. 40 of 1999 concerning the press, Law No. 32 of 2002 concerning broadcasting, Law No. 11 of 2008 concerning information and electronic transactions, and Law No. 44 of 2008 concerning pornography. The existing positive criminal law governing pornography is silent on the principles used to define criminal activities and criminal responsibility. This situation frequently results in disagreements and also divergent approaches to the enforcement of criminal law in Indonesia.